UNDERSTANDING THE DIFFICULTIES FACED BY EFL STUDENTS IN WRITING COMPOUND-COMPLEX SENTENCES IN ACADEMIC WRITING - Agus Hidayat (COMPASS: Journal of Education and Counselling, 2025)
This study looked at the problems EFL (English as a Foreign Language) students had in writing compound-complex sentences in academic writing. The main aim was to know both grammar problems and students’ feelings when they try to use this difficult sentence type. The researcher used a qualitative narrative inquiry method to collect deep information from semi-structured interviews and reflective journals. Participants were chosen with purposive sampling to show different levels of English skill. Thematic analysis helped to find main problems in their writing. The findings showed that most students had trouble using conjunctions in the right way, knowing the difference between independent and dependent clauses, and using punctuation correctly. Around 75% of the students said they found it hard to write compound-complex sentences. More than 60% also felt confused about how to use punctuation. The students’ first language also gave influence, and many said the teacher's feedback was not always clear. Emotional problems like fear and low confidence also made it harder for students. Working together and doing writing practice many times helped improve their writing and gave them more confidence. Students also said they wanted more clear lessons and useful workshops about sentence types. This study shows that students need special help from teachers to learn how to build compound-complex sentences, so their academic writing can be better.